PISANG-PISANGAN (MUSACEAE) DI GUNUNG WATUWILA DAN DAERAH SEKITARNYA - Lulut D. Sulistyaningsih (Floribunda, 2012)
Knowledge of Sulawesi’s flora including bananas is rather poor due to lack of botanical exploration in this area. Exploration to assess the diversity of bananas in Mount Watuwila and adjacent areas has been done. Two intraspecific taxa of wild banana species (Musa acuminata var. tomentosa and M. acuminata ssp. banksii) and twelve banana cultivars occur in these area. Musa acuminata Colla var. tomentosa is an endemic variety of wild banana species in Sulawesi. Variation on some characters found in M. acuminata var. tomentosa. Some of the banana cultivars are members of M. acuminata triploid AAA, M. balbisiana triploid BBB, and Musa x paradisiaca triploid AAB.